Cadmium in Brown Crab Cancer pagurus in Norwegian Waters - Wiech, Martin (Aquatic Toxicology, 2018)
The Brown crab Cancer pagurus is appreciated as seafood and its fishery is of importance in several European countries. However, findings of high levels of cadmium have increased concern about food safety, and spatial patterns of cadmium levels have been found. Along the Norwegian coast, a sudden spatial increase in cadmium levels in brown crab from Salten region in Northern Norway (ca. 67°N) and northwards has been identified. An earlier study including sediment measurements investigated the reason for the high values in the North, and concluded that it is unlikely that an anthropogenic point source is responsible for the high cadmium levels. The main aim of this thesis was to investigate further factors that may explain the large variation of cadmium in brown crab, and whether these factors can explain the differences in cadmium levels in brown crab along the Norwegian coast, with focus on physiological factors. Conflicting values of reported cadmium levels in crab claw meat led us to evaluate the pretreatment of crabs before analyses. A strong effect of cooking and freezing was found, causing a leakage of cadmium from hepatopancreas to claw meat. The findings in crabs sampled in the North and the South of the Norwegian coast during one year, revealed that the influence of physiological factors on cadmium levels is not very pronounced in comparison to the large differences between crabs from the North and the South. However, there was a correlation between size and cadmium levels in crabs sampled in the North, indicating an accumulation of cadmium over time. As brown crabs are assumed to grow more slowly in the North, this indicates that some of the variation in cadmium between the North and the South can be explained by growth rate. Further evidence for a high potential of brown crab to accumulate cadmium has been found in a lab trial, where cadmium from food and water was traced in brown crab to compare the relative importance of the uptake routes. No depuration of cadmium was observed, indicating a high ...